Sexual Violence Crime Reform in Indonesia: Political and Legal Characteristics of Its Formation - Abshar, Rijal Ulil (As-Siyasi: Journal of Constitutional Law, 2024)
Handling sexual violence and gender-based violence remains a significant issue in Indonesia. The state plays a crucial role in ensuring the enforcement of laws against sexual violence by enacting Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS). This study aims to identify the legal characteristics of UU TPKS. The study employs the literature review method. This research is descriptive-analytic, focusing on normative juridical legal research. The results show that the state is obliged to provide human rights protection, particularly in the context of eliminating sexual violence. UU TPKS is characterized as a responsive legal product. It fulfils the state's duty to provide comprehensive legal protection, encompassing prevention, resolution, and mitigation of both psychological and material losses suffered by victims of sexual violence due to the introduction of new formulations regarding sexual violence crimes that were not present in previous legislation. The criminal law reform in UU TPKS aims to change the existing legal substance to enhance the effectiveness of law enforcement, address crime, and tackle social and humanitarian issues. UU TPKS will become the primary and foremost special regulation in combating Sexual Violence Crimes, complementing the existing legislation that previously regulated the substance of sexual violence crimes.